Comparison between the Bouchama and Japanese Association for Acute Medicine Heatstroke Criteria with Regard to the Diagnosis and Prediction of Mortality of Heatstroke Patients: A Multicenter Observational Study - Yutaka Kondo (International Journal of Environmental Research and Public Health, 2019)
Background: This study aims to compare the Bouchama heatstroke (B-HS) and Japanese Association for Acute Medicine heatstroke (JAAM-HS) criteria with regard to the diagnosis and prediction of mortality and neurological status of heatstroke patients. Methods: This multicenter observational study recruited eligible patients from the emergency departments of 110 major hospitals in Japan from 1 July to 30 September, 2014. Results: A total of 317 patients (median age, 65 years; interquartile range, 39−80 years) were included and divided into the B-HS, JAAM-HS, and non-HS groups, with each group consisting of 97, 302, and 15 patients, respectively. The JAAM-HS (1.0; 95% confidence interval [CI], 0.87−1.0) and B-HS (0.29; 95% CI, 0.14−0.49) criteria showed high and low sensitivity to mortality, respectively. Similarly, the JAAM-HS (1.0; 95% CI, 0.93−1.0) and B-HS (0.35; 95% CI, 0.23−0.49) criteria showed high and low sensitivity to poor neurological status, respectively. Meanwhile, the sequential organ failure assessment (SOFA) scores demonstrated good accuracy in predicting mortality among heat-related illness (HRI) patients. However, both JAAM-HS and B-HS criteria could not predict in-hospital mortality. The AUC of the SOFA score for mortality was 0.83 (day 3) among the HRI patients. The patients’ neurological status was difficult to predict using the JAAM-HS and B-HS criteria. Concurrently, the total bilirubin level could relatively predict the central nervous system function at discharge. Conclusions: The JAAM-HS criteria showed high sensitivity to mortality and could include all HRI patients who died. The JAAM-HS criterion was considered a useful tool for judgement of admission at ED. Further investigations are necessary to determine the accuracy of both B-HS and JAAM-HS criteria in predicting mortality and neurological status at discharge.